"The world is a perfect animal." Politics and biology in the Stoics - Nava Contreras, Mariano (2023)
This paper attempts to review the Stoic conception of the universe as an immense sentient animal provided with thoughtand perfection to the highest degree, as formulated by Sextus Empiricus in Adv. Math. IX 88 = SVF I 529. This idea has its roots in Aristotelian biology and naturalism, although it was the Stoics who developed it as part of their political thought, with important connotations not only for politics and biology, but also for its ethical, physical and cosmological system. Thisconception constitutes one of the first attempts to establish a relationship between politics and biology in Greek thought.